THE TOXICITY EFFECT OF MONOCROTOPHOS 36% E. C ON THE HAEMATOLOGY, LABEO ROHITA (HAMILTON, 1882) - Tamizhazhagan, V. (International Journal of Current Pharmaceutical Research, 2015)
Objective: Pesticides are stable compounds and they enter the aquatic ecosystem through the agriculture run off. The evaluation of nature and degree of harmful effects produced by the toxic substance in the aquatic organisms are evaluated by toxic tests. The 96 hour LC50 values have generally been found to be satisfactory for the measurement of acute toxicity. The differences in 96 h LC50 of the same toxicant in different fishes may be attributed to individual traits including those of behavior and additional structure such as accessory respiratory organs. The individual characters such as size and weight, sex and biological behavior are important determination for variation in LC50 values. Methods: Therefore, in this present study is an attempt to study the toxicity of the pesticide with respect to the hematology, biochemical and histology of fish Labeo rohita (Ham). The Monocrotophos affects not only fish but also organisms in the food chain through the process of consumption of one by the other. The pesticide, which enters the body tissues of the fish, affects the physiological activities. Results: The cytometric measurements of erythrocytes of sublethal exposure showed that there is not much differences from the control. In the control fish, the erythrocytes were oval in shape with elongated nucleus. Fish, exposed to sublethal concentration of Monocrotophos showed abnormal size Reduction in the volume of the cytoplasm of cells and swelling of nuclei were observed in fish exposed to concentration. In the hematology, the total Red Blood Corpuscle and Haemoglobin content were decreased with the increasing hours of exposure of the monocrotophos 36% EC. The amount of the Mean Corpuscular Haemoglobin (MCH) also was increased. The haemoglobin content directly relationship for RBC content it indicate count leading to anemia as a result of inhibition of erthropoiesis, haemosynthesis and increase in the rate of erythrocyte destruction in haemopoietic organs. However, the total was total White Blood Corpuscle was increased with the increasing hours of exposure of the Monocrotophos 36% E. C. The constant increasing in the differential count clearly indicates that the pesticide stress certainly stimulate the white blood cells to produce more at all time of exposure. A linear relationship was established with respect to pesticide monocrotophos and total White Blood Corpuscle. The constant increase in the differential count clearly indicates that the pesticide stress certainly stimulate the white blood cells to produce more at all times of exposure. Conclusion: It has been suggested that the enumeration of differential cell ratio counts provide of useful diagnostic procedure to assess the physiological stress in the fish.